Pengaruh Kualitas Produk, Harga, Dan Citra Merek Terhadap Keputusan Pembelian Lipstik Wardah - Natasya Aulia Putri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of product quality, price, and brand image variables on the purchase decision of wardah lipstick. Both partially and simultaneously. Data collection was carried out by distributing questionnaires that had been distributed to 47 respondents. By using a Likert scale, the respondents' answers were processed using multiple regression analysis, t-test, f-test, and r-test. The results of this study can be found that there is a significant (significant) effect partially.